Estimating distribution and connectivity of recolonizing American marten in the northeastern United States using expert elicitation techniques. (16th April 2018) - Aylward, C. M.; Murdoch, J. D.; Donovan, T. M.; Kilpatrick, C. W.; Bernier, C.; Katz, J.
Abstract: The American marten Martes americana is a species of conservation concern in the northeastern United States due to widespread declines from over‐harvesting and habitat loss. Little information exists on current marten distribution and how landscape characteristics shape patterns of occupancy across the region, which could help develop effective recovery strategies. The rarity of marten and lack of historical distribution records are also problematic for region‐wide conservation planning. Expert opinion can provide a source of information for estimating species–landscape relationships and is especially useful when empirical data are sparse. We created a survey to elicit expert opinion and build a model that describes marten occupancy in the northeastern United States as a function of landscape conditions. We elicited opinions from 18 marten experts that included wildlife managers, trappers and researchers. Each expert estimated occupancy probability at 30 sites in their geographic region of expertise. We, then, fit the response data with a set of 58 models that incorporated the effects of covariates related to forest characteristics, climate, anthropogenic impacts and competition at two spatial scales (1.5 and 5 km radii), and used model selection techniques to determine the best model in the set. Three top models had strong empirical support, which we model averaged based on AIC weights. The final model included effects of five covariates at the 5‐km scale: percent canopy cover (positive), percent spruce‐fir land cover (positive), winter temperature (negative), elevation (positive) and road density (negative). A receiver operating characteristic curve indicated that the model performed well based on recent occurrence records. We mapped distribution across the region and used circuit theory to estimate movement corridors between isolated core populations. The results demonstrate the effectiveness of expert‐opinion data at modeling occupancy for rare species and provide tools for planning marten recovery in the northeastern United States. Abstract : American marten occupancy was estimated across the northeastern United States from expert‐opinion data using mixed‐effects modeling techniques. Top‐performing models included predictor variables of tree canopy cover, spruce‐fir land cover, elevation, temperature and road density. In our expert survey, experts with primarily field‐based expertise made higher site‐occupancy estimates than experts with literature‐based expertise.